Զգայական ընկալման բառերի ոճական արժեքը Պարույր Սևակի չափածոյում - Գրիգորյան, Սուսաննա
В поэзии П. Севака много языковых структур, которые выражают чувственные восприятия. Они являются богатым материалом для морфологических и синтаксических, стилистических исследований. Стилистическая значимость слов, выражающих чувственные восприятия, в поэзии Севака выражается эпитетам и ,сравнениями, метафорами, перифразами и фразеологическим и оборотами. Мы исследовали также словообразовательные особенности этих единиц. Отмечены авторские неологизмы, например: боцбег, хнкацавал, дарнаперч, шаганаке и т.д. P. Sevak's poetics is rich in linguistic structures expressing sensual perceptions which serve as a serious subject for investigation from morphological, syntactic as well as from stylistic points o f view. The stylistic value o f the words expressing sensual perception in P. Sevak's poetics is notable for revealing epithets, metaphors, similes, paraphrases and phraseological units. The word-formation o f the units under study is also taken into consideration. We have also considered the author neologisms among which are words like-botsbegh, khnkatsaval, damaperch, shaganake and so on.
Keywords: Լեզու և գրականություն; Ոճաբանություն